2017
DOI: 10.1089/end.2016.0396
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Classification Scheme for Examining Adverse Events Associated with Medical Devices, Specifically the DaVinci Surgical System as Reported in the FDA MAUDE Database

Abstract: Our classification system is a valid tool with moderate inter-rater agreement that can be used to better understand device-related adverse events. The majority of robotic related events were mild but associated with the device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…The introduction of devices following clearance is unstructured and variable; more often than not, their use is reported in non-comparative trials without institutional board review. This process carries an obvious risk to patient safety, and a number concerns have been raised regarding the lack of centralised adverse event reporting [ 30 ]. To address this shortfall, the Balliol Collaboration has proposed the IDEAL model for safe innovation [ 3 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of devices following clearance is unstructured and variable; more often than not, their use is reported in non-comparative trials without institutional board review. This process carries an obvious risk to patient safety, and a number concerns have been raised regarding the lack of centralised adverse event reporting [ 30 ]. To address this shortfall, the Balliol Collaboration has proposed the IDEAL model for safe innovation [ 3 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Connor applied Chi‐Square, Kolmogorov‐Smirnov, and regression in the review of device‐class specific reports and recalls in MAUDE. Also in 2017, Gupta et al applied Chi‐Square along with manual classification to monitor MAUDE AEs …”
Section: Discussionmentioning
confidence: 99%
“…Registries as defined for this review included hospital and provider case series and medical‐record based data. MAUDE represented the second most common data source with eight studies from 1998 to 2017 representing 8% of articles reviewed …”
Section: Summary Of Reviewed Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Agcaoglu and colleagues, reporting on malfunction and failure of robotic systems, described a 4·5 per cent incidence of these events, related to instruments, optical system, arms and the console. Recently Gupta and co‐workers found that 77 per cent of adverse events during RAS were classified as being definitely related to the device, 15 per cent as possibly related and 8 per cent as not related. Using the results from a specialized centre as part of informed consent can misrepresent these risks and outcomes for patients.…”
mentioning
confidence: 99%